Antifungal Activity and Mechanism of Action of the Co(III) Coordination Complexes With Diamine Chelate Ligands Against Reference and Clinical Strains of Candida spp. - Turecka, Katarzyna; Chylewska, Agnieszka; Kawiak, Anna; Waleron, Krzysztof F. (Frontiers in Microbiology, 2018)
Although many antifungal agents are available in clinical treatment, increasing resistance of fungi, especially Candida species, to the available drugs requires the development of new safe and non-toxic compounds with novel modes of action as effective treatment against resistant microorganisms. Cobalt complexes are very interesting and attractive as potential candidates with antimicrobial activity. Their therapeutic uses as antiviral, antibacterial antifungal, antiparasitic, antitumour, transferrin transporters and anti-inflammatory agents are being intensively investigated. In this study we examined the antifungal activity of Co(III) complexes with diamine chelate ligands against a broad spectrum of Candida species. Minimum inhibitory concentration was determined by the microbroth dilution method and with serial passaging assay; the synergistic antimicrobial activity of the tested complexes combined with two antifungal drugs (ketoconazole and amphotericin B) was made by checkerboard assay. The effects of Co(III) complexes on yeast cell morphology were studied by optical and transmission electron microscopy. The mode of action of Co(III) complexes on the yeast cell wall (sorbitol assay) and cell membrane (ergosterol assay) were investigated. The cytotoxic effects of the tested compounds on red blood cells and the human keratinocyte (HaCaT) cell line were also evaluated. The analysed compounds revealed significant antifungal activity for selected strains of Candida species; [CoCl2(dap)2]Cl (1) and [CoCl2(en)2]Cl (2) were more effective than ketoconazole. Its probable mechanism of action did not involve the cell wall or ergosterol binding. However, the checkerboard assay showed, that the antifungal activity of ketoconazole increased in combination with the tested complexes of Co(III). Our results suggest that both diamine complexes with Co(III) analogues caused damage to mitochondrial membrane or the membrane of the endoplasmic reticulum. The effect was observed by transmission electron microscope. Co(III) complexes with diamine chelate ligands are non-toxic at concentrations active against Candida species. This study provides new data on potential antifungal drugs, especially against Candida species.